Legal and Technological Approaches to Cybercrime Risk Mitigation: A Case Study of Cyber Law and Cybersecurity Implementation in Southeast Asia (Open Society Conference, 2025)
This study examines the integration of legal and technological approaches in mitigating the risks of cybercrime, with a focus on the implementation of cyber law regulations and cybersecurity technology in the Southeast Asian region. The study uses normative research methods and case studies, examining various legal policies, regulations, and technological security practices in ASEAN countries. The research findings indicate that the increasing threat of cybercrime necessitates the harmonization of cross-border legal regulations and the implementation of adaptive and collaborative cybersecurity technologies. However, there are significant challenges related to the imbalance in technological capacity and law enforcement among countries, as well as limitations in regional coordination. The study emphasizes the importance of synergy between a strong legal framework, enhanced technical capacity, and inter-state cooperation to create a secure and resilient digital ecosystem against cybercrime threats. Strategic recommendations are provided to strengthen policy harmonization, develop cybersecurity infrastructure, and enhance awareness and capacity among law enforcement agencies in Southeast Asia.